RELATIONSHIP BETWEEN PRENATAL EXERCISE AND SLEEP QUALITY IN PREGNANT MOTHERIN THE WORKING AREA OF BANDAR KHALIPAH HEALTH CENTER IN 2025: HUBUNGAN SENAM HAMIL DENGAN KUALITAS TIDUR IBU DI WILAYAH KERJA PUSKESMAS BANDAR KHALIPAH KABUPATEN DELI SERDANG TAHUN 2025 - Samsider Sitorus; Julietta Hutabarat; Safira Rahmi (Poltekkes Kemenkes Medan, 2026)
Sleep quality issues are a common complaint among pregnant mother, especially in the second and third trimesters, which can affect the health of both the mother and the fetus. This study aimed to determine the relationship between prenatal exercise and sleep quality in pregnant women in the working area of the Bandar Khalipah Public Health Center, Deli Serdang Regency. The research method used was quantitative with a cross-sectional approach. The sample consisted of 42 pregnant mother selected using a purposive sampling technique. Data collection instruments included a questionnaire distributed before and after the prenatal exercise program. The data were analyzed univariately and bivariately using the chi-square test. The results showed that the majority of respondents did not regularly perform prenatal exercise (69%) and had poor sleep quality (57.1%). The bivariate analysis results indicated a significant relationship between prenatal exercise and the sleep quality of pregnant mother (p=0.007). It can be concluded that prenatal exercise has a positive effect on improving the sleep quality of pregnant mother. Therefore, it is recommended that pregnant women regularly participate in prenatal exercise as a non-pharmacological effort to improve their sleep quality.